The Effects of a Game-Based Web Application on EFL Students’ Vocabulary Mastery: A Quasi- Experimental Study - Rahadatul Aisy; Dzakiah Dzakiah; Rasmi Rasmi (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Vocabulary mastery is essential for learning English as it supports the development of the four language skills. However, many Indonesian students face difficulties due to uninteresting instruction and low motivation. This study aimed to examine the effect of a game-based web application (Wordwall) on the vocabulary mastery of EFL students. A quantitative quasi-experimental design was employed involving two classes consisting of 32 students each. The experimental group was taught using Wordwall, while the control group received conventional instruction. Vocabulary mastery was measured through pre-test and post-test instruments. The findings revealed that the experimental group showed significantly greater improvement than the control group, with mean post-test scores of 74.37 and 59.38, respectively. Statistical analysis confirmed that there was a significant effect of using Wordwall on students’ vocabulary mastery (t = 14.883, p < 0.05). Furthermore, the effect size analysis using Cohen’s d indicated a large effect (d = 0.86). These findings demonstrate that the use of Wordwall as a game-based web application has a significant effect on EFL students’ vocabulary mastery at the junior high school level.